ANALISIS MATEMATIKA PADA PENETAPAN MATAHARI DAN BULAN SEBAGAI PENGUKURAN WAKTU DALAM SURAH YUNUS AYAT KE-5 - Hanifa; Jadid Khadavi, M. (As-Sulthan Journal of Education, 2025)
This study aims to examine Surah Yunus verse 5 from the perspective of mathematics and modern science, highlighting the order of the sun and moon as a time-measuring system. This verse explains the astronomical role of these celestial bodies, which serve as the foundation for lunar and solar calendar systems in human civilization. Using a qualitative approach, this research integrates tafsir analysis, literature review, and philosophical reflection to interpret the cosmic order established by Allah. The findings indicate that the verse aligns with modern scientific principles, including the laws of gravity and orbital cycles, demonstrating a systematic structure in the universe. This order not only serves as evidence of Allah's greatness but also teaches the importance of time consciousness as a divine blessing that must be utilized wisely. Furthermore, the study affirms that the integration of science and spirituality in the Qur’an contributes to scientific and educational advancements. Thus, this research reinforces the Qur’an’s relevance as a timeless source of knowledge that continues to inspire both scientific understanding and spiritual life.